On the possibility for the resonance ELM-generation mechanism by the injection of the neutral particle beam in tokamak - Gordeev, A.V. (Вопросы атомной науки и техники, 2007)
It is known that in plasmas with a magnetic field the Hall electric field is generated at the expense of the charge separation on the magnetic Debye radius rB=|B|/(4pene). In addition, the plasma current equilibrium can arise, where the charged particles are drifting in the crossed electric and magnetic fields. Such a situation can be realized in tokamaks as a result of the ionization processes for the beams of the energetic neutral particles that are injected in tokamaks in order to increase the plasma density and temperature. In this presentation, the generation of the resonance instability for the azimuthal drifting flux of the ions and electrons crosswise to the strong magnetic field is considered.